Perbedaan Tinggi, Jumlah Daun, dan Diameter Batang Tanaman Jagung (Zea mays L.) pada Sistem Agroforestri Penanaman Lorong (Alley Cropping) dan Tumpang Sari di DAS Mikro Desa Tukad Sumaga, Kecamatan Gerokgak, Kabupaten Buleleng - WIRYANATA, I WAYAN GEDE; ASTUTHI, MADE MIKA MEGA; DEWI, KADEK AYU CHARISMA JULIA (Agrotrop : Journal on Agriculture Science; Vol 11 No 2 (2021), 2021)
Differences in Height, Number of Leaves, and Stem Diameter of Corn ( Zea mays L.) in Alley Cropping and Intercropping of Agroforestry Systems at the Micro Watershed of Tukad Sumaga Village, Gerokgak District, Buleleng Regency . Degraded land as a result of land conversion has a very bad impact on the agro-ecosystem. Land conversion caused by the increasing needs of the population. The majority of the livelihoods of the people in Tukad Sumaga village are farmers. The availability of forage is very important to be maintained. Corn plants, in addition to their production in the form of corn, forage fodder on corn plants are very important for the availability of cattle feed. This research was conducted on 28 DAP maize ( Zea mays L.) in alley cropping system and intercropping in the micro watershed of Tukad Sumaga Village. The results showed that the highest average plant height, leaf number, and corn stalk diameter were found in the alley cropping system namely 1.03 m, 7.31, and 1.59 cm. There was no significant difference between the height of corn plants in alley cropping and intercropping systems. There is a significant difference between the number of leaves and the diameter of the stems of maize in alley cropping and intercropping systems.